Lung volume reduction eligibility in patients with COPD completing pulmonary rehabilitation: results from the UK National Asthma and COPD Audit Programme - Buttery, Sara C (BMJ Open, 2020)
OBJECTIVES: To establish what proportion of patients completing a UK pulmonary rehabilitation (PR) programme meet the 2018 National Institute for Health and Care Excellence (NICE) chronic obstructive pulmonary disease (COPD) guideline (NG115) criteria to have a respiratory review to establish whether referral to a lung volume reduction multidisciplinary team would be appropriate. This respiratory review would include evaluation of the presence of hyperinflation and the presence of emphysema on CT scan. The NICE criteria include measures of breathlessness and exercise capacity but these parameters are not completely defined. DESIGN: Observational study. SETTING: PR programmes across the UK in 2015 (210 centres) and 2017 (184 centres) entering data into the Royal College of Physicians’ National Asthma and COPD Audit Programme. PARTICIPANTS: 8295 (55.7%) of 14 889 patients in programmes using incremental shuttle walk test (ISWT) or 6-minute walk test (6MWT) as an outcome measure completed PR, and 4856 (32.6%) had complete data recorded (6MWT/ISWT, baseline spirometry, Medical Research Council (MRC) dyspnoea score). RESULTS: Depending on the walking test safety threshold adopted for the ISWT (≥140 m or ≥ 80 m) and the MRC dyspnoea score threshold used (MRC score ≥3 or ≥4 at the end of PR), between 4.9% and 18.1% of PR completers met the NICE criteria for a lung volume reduction-focused respiratory review. CONCLUSIONS: Lung volume reduction therapies are beneficial in appropriately selected patients with COPD, but few procedures are performed, and treatment pathways are unclear. These data help to inform the feasibility of the approach recommended by NICE and highlight the need for future systematic pathways to reduce inequalities in patients being considered for effective treatments.